2020
DOI: 10.3390/ijerph17249234
|View full text |Cite
|
Sign up to set email alerts
|

B-Comet Assay (Comet Assay on Buccal Cells) for the Evaluation of Primary DNA Damage in Human Biomonitoring Studies

Abstract: Many subjects perceive venous blood collection as too invasive, and thus moving to better-accepted procedures for leukocytes collection might be crucial in human biomonitoring studies (e.g., biomonitoring of occupational or residential exposure to genotoxins) management. In this context, primary DNA damage was assessed in buccal lymphocytes (BLs), fresh whole venous, and capillary blood leukocytes, and compared with that in peripheral blood lymphocytes (PBLs)—the most frequently used cells—in 15 young subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Recently, human salivary leucocytes have been proposed as a non-invasive adequate alternative to peripheral blood leucocytes to evaluate the genotoxic effects of recent exposure to environmental contaminants, particularly those involving inhalatory or oral exposure routes [ 13 ]. Moreover, this cell type might be also useful for in vitro testing, and indeed our group has recently proved that leucocytes isolated from saliva samples, both fresh and cryopreserved, can be employed as appropriate biomatrices to detect primary and oxidative DNA damage caused by different mechanisms by the comet assay [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, human salivary leucocytes have been proposed as a non-invasive adequate alternative to peripheral blood leucocytes to evaluate the genotoxic effects of recent exposure to environmental contaminants, particularly those involving inhalatory or oral exposure routes [ 13 ]. Moreover, this cell type might be also useful for in vitro testing, and indeed our group has recently proved that leucocytes isolated from saliva samples, both fresh and cryopreserved, can be employed as appropriate biomatrices to detect primary and oxidative DNA damage caused by different mechanisms by the comet assay [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…And Zani et al (2020) evaluated the effects of air pollution in salivary leucocytes (directly obtained from mouthwashes, without isolation) of exposed pre-school children, observing no significant association between air pollution and DNA damage. Furthermore, although buccal leucocytes obtained from smokers and analysed by the comet assay were reported to have more DNA damage than cells from non-smokers (Oßwald et al 2003), more recent studies showed that comet parameters evaluated in salivary leucocytes are not influenced by sex, age, smoking habit, diet, alcohol consumption or body mass index (McCauley et al 2008;Russo et al 2020). All these studies demonstrate the feasibility of using salivary leucocytes in the comet assay for human population studies.…”
Section: Discussionmentioning
confidence: 84%
“…Still, the similar results regarding sensitivity to DNA damage induction by the three different agents-MMS, Act-D and UV lightobtained in the three sample types support the possibility of using salivary leucocytes as a good alternative or complement to blood samples. According to these results, Russo et al (2020) compared recently the basal level of primary DNA damage in salivary leucocytes and isolated PBL (both freshly obtained) from 15 young subjects, to found that the two sample types provide similar measures, as the level of agreement (calculated by the Bland-Altman method) lied within the accepted range.…”
Section: Discussionmentioning
confidence: 95%
“…Most human studies have focused on blood cells because they are easy to obtain, and—as they circulate in the body—the metabolic state of these cells can reflect the overall extent of body exposure [ 17 ]. However, other cell types have also been employed, such as buccal, nasal, lens epithelial, and germ cells [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%